1998
DOI: 10.1007/bf02355530
|View full text |Cite
|
Sign up to set email alerts
|

Some features of formation of the structural strength of ceramic materials

Abstract: On the basis of preliminary investigations of the characteristics of the crack-propagation resistance of various types of ceramic and cermet materials, we give a general evaluation of their potentialities in the context of the influence of the structural-metallurgical factor and the micromechanisms of fracture on the serviceability of the materials. We propose to evaluate the mechanical efficiency of ceramic materials by comparing their diagrams of structural strength at room and service temperatures. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The authors showed that additions of 10–20% ZrO 2 efficiently inhibited the growth of Al 2 O 3 crystals and, thus, positively affected the mechanical behavior of the ceramics. In Reference [ 32 ], the authors have proved that the optimal mechanical properties of zirconia ceramics and alumina doped with zirconia should be determined by estimating both the fracture toughness and strength characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that additions of 10–20% ZrO 2 efficiently inhibited the growth of Al 2 O 3 crystals and, thus, positively affected the mechanical behavior of the ceramics. In Reference [ 32 ], the authors have proved that the optimal mechanical properties of zirconia ceramics and alumina doped with zirconia should be determined by estimating both the fracture toughness and strength characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…It is critically important to manufacture materials resistive to the aggressive operating environment [35][36][37][38] to avoid microstructure degradation [39][40][41][42]. Therefore, along with strength and tribology tests of materials as the most popular methods for diagnosing their load-bearing capacity, the indentation test, known as the simplest mechanical method [39,43], is widely used.…”
Section: Introductionmentioning
confidence: 99%
“…The specimens were tested according to a three-point bend scheme in a temperature range 20-1000 °C. Based on the "loadflexure" dependences, the fracture stress (σf ) was calculated by the following equation [24,31,35,75]:…”
Section: Methodsmentioning
confidence: 99%
“…Besides, distinct "needle-shaped Cr2AlC phase-Ti(Cr) matrix" interfaces disappeared due to the interdiffusion of chromium, aluminum, and oxygen between the chromium oxide phase, the Cr2AlC MAX phase, and the matrix phase. This, in turn, caused a change in the fracture micromechanism [54,75]. In this composite, high-temperature fracture occurred at 800 °C (Fig.…”
Section: Ti-si-al-zr-c Composite (3)mentioning
confidence: 95%
See 1 more Smart Citation